MODEL ALOMETRIK PENDUGA ABOVEGROUND BIOMASS Gigantochloa atter DI DESA ALU, KABUPATEN POLEWALI MANDAR - Irundu, Daud; HM, Rahmania; Wahyudi, Wahyudi; Ritabulan, Ritabulan; Alviani, Mila (Gorontalo Journal of Forestry Research, 2024)
Biomass allometric models are needed to determine the carbon content absorbed by bamboo plants. There are still many bamboo plants that do not have a local allometric model to estimate their biomass, one of which is Gigantochloa atter bamboo. This research aims to produce an allometric model for estimating the biomass of Gigantochloa atter bamboo found in Alu Village, Polewali Mandar Regency, West Sulawesi Province. Dustructive sampling method of 30 bamboo plants, to obtain wet weight and water content, starting with measuring the diameter and total height. Water content to determine biomass. Biomass, diameter and height values were analyzed by regression to develop allometric models according to predetermined equations. Substitution of measurement values into the allometric equation and data analysis using the coefficient of determination (R2), bias, error index and Mean Square Error Prediction variable scoring method. The scoring results of six models for estimating the biomass of Gigantochloa atter bamboo plants in Alu Village, Polewali Mandar Regency were selected as the best model Y = 0.785+0.011(D2H) with the highest score values including R2 value (0.982), Bias value (0.124), IE value (25.086) and MSEP (1.435).